2020 EULAR points to consider for the prevention, screening, assessment and management of non-adherence to treatment in people with rheumatic and musculoskeletal diseases for use in clinical practice. Issue 6 (18th December 2020) - Ritschl, Valentin; Stamm, Tanja A; Aletaha, Daniel; Bijlsma, Johannes W J; Böhm, Peter; Dragoi, Razvan Gabriel; Dures, Emma; Estévez-López, Fernando; Gossec, Laure; Iagnocco, Annamaria; Marques, Andrea; Moholt, Ellen; et al.
Abstract : Background: Non-adherence to treatment could preclude reaching an optimal outcome. Thirty to 80% of patients with rheumatic and musculoskeletal diseases (RMDs) do not adhere to the agreed treatment. Objectives: The objective was to establish points to consider (PtCs) for the prevention, screening, assessment and management of non-adherence to (non-)pharmacological treatments in people with RMDs. Methods: An EULAR task force (TF) was established, and the EULAR standardised operating procedures for the development of PtCs were followed. The TF included healthcare providers (HCPs), comprising rheumatologists, nurses, pharmacists, psychologists, physiotherapists, occupational therapists and patient-representatives from 12 European countries. A review of systematic reviews was conducted in advance to support the TF in formulating the PtCs. The level of agreement among the TF was established by anonymous online voting. Results: Four overarching principles and nine PtCs were formulated. The PtCs reflect the phases of action on non-adherence. HCPs should assess and discuss adherence with patients on a regular basis and support patients to treatment adherence. As adherence is an agreed behaviour, the treatment has to be tailored to the patients' needs. The level of agreement ranged from 9.5 to 9.9 out of 10. Conclusions: These PtCs can help HCPs to support people with RMDs to be more adherent to the agreed treatment plan. The basic scheme being prevent non-adherence by bonding with the patient and building trust, overcoming structural barriers, assessing in a blame-free environment and tailoring the solution to the problem.